Chinese religion(s): a survey of textbooks. Issue 3 (2nd July 2016) - Cheung, Kin; Valerio, Adam; Kunu, Vishma; Bingenheimer, Marcus
ABSTRACT: This paper surveys five introductory textbooks on Chinese religion(s) published over the past 25 years. For instructors choosing a textbook, we provide a comparison of each work's format and content, remark on their suitability for meeting various pedagogical objectives, and reconsider the purpose of university textbooks in the context of new developments in knowledge production and accessibility. Moreover, we argue that these surveyed works reflect a change in scholarly consensus within the field. The trend has shifted from describing Chinese religion(s) as a unified whole to that of a conglomerate: discrete traditions of Confucianism, Buddhism, Daoism, and popular-folk religion. Although specialists complicate hard distinctions between these traditions through highlighting shared influences and developments, the general presentation of Chinese religion(s) has shifted from a synthetic whole to analytic parts.